Effect of drying methods on the structure, thermo and functional properties of fenugreek (Trigonella foenum graecum) protein isolate. (19th October 2017) - Feyzi, Samira; Varidi, Mehdi; Zare, Fatemeh; Varidi, Mohammad Javad
Abstract: BACKGROUND: Different drying methods due to protein denaturation could alter the functional properties of proteins, as well as their structure. So, this study focused on the effect of different drying methods on amino acid content, thermo and functional properties, and protein structure of fenugreek protein isolate. RESULTS: Freeze and spray drying methods resulted in comparable protein solubility, dynamic surface and interfacial tensions, foaming and emulsifying properties except for emulsion stability. Vacuum oven drying promoted emulsion stability, surface hydrophobicity and viscosity of fenugreek protein isolate at the expanse of its protein solubility. Vacuum oven process caused a higher level of Maillard reaction followed by the spray drying process, which was confirmed by the lower amount of lysine content and less lightness, also more browning intensity. Δ H of fenugreek protein isolates was higher than soy protein isolate, which confirmed the presence of more ordered structures. Also, the bands which are attributed to the α‐helix structures in the FTIR spectrum were in the shorter wave number region for freeze and spray dried fenugreek protein isolates that show more possibility of such structures. CONCLUSION: This research suggests that any drying method must be conducted in its gentle state in order to sustain native structure of proteins and promote their functionalities. © 2017 Society of Chemical Industry